Pesticides: a two-edged sword - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Insects, diseases, and weeds account for 40% of the annual crop and harvest losses in the ACP countries. But the use of pesticides, the most commonly adopted remedy against these scourges, has its dangers both for man and environment The only way to...